CerS6-derived sphingolipids interact with Mff and promote mitochondrial fragmentation in obesity - Hammerschmidt, Philipp; Schweinfurth, Daniela; Brügger, Britta (Cell, 2019)
Ectopic lipid deposition and altered mitochondrial dynamics contribute to the development of obesity and insulin resistance. However, the mechanistic …